Optical Vibration Sensor Module Based on Beating Principle for Monitoring of Semiconductor Manufacturing Equipment - Moon, Kee S.; Lee, Moon Gu (International Journal of Precision Engineering and Manufacturing, 2024)
Autonomous preventive maintenance (APM) is important for modern semiconductor manufacturing equipment to enhance yield. APM involves detecting various signals from the equipment’s components and/or the workpiece to monitor equipment health in real time and perform adequate maintenance. This paper proposes a vibration sensor module with noncontact sensing capability that is small, simple, and highly sensitive. The module’s hardware includes two sensor components, which are a combination of a small infrared light- emitting device (IR LED) and a photodetector (PD). The module performs sensing based on the principle of beating. Compared with conventional direct sensing, the proposed module achieves a fourfold improvement in sensitivity and a 3.5-improvement in signal-to- noise ratio. Moreover, the small size of the IR LED and PD die chips can enable miniaturization. If a sensor system combining the proposed sensor module with a microcontroller unit and a transceiver is integrated into semiconductor manufacturing equipment, independent and remote APM can be easily and widely realized.
Keywords: Beating principle; Infrared light; Light-emitting device; Manufacturing equipment; Module-based; Optical vibration sensor; Optical vibrations; Semiconductor manufacturing; Sensor modules; Vibration sensors; Beating principle; Optical vibration sensor; Preventive maintenance; Semiconductor manufacturing